Intralymphatic Immunotherapy: update and unmet needs - Senti, Gabriela; Pfaar, Oliver (International archives of allergy and immunology, 2019)
Allergen-specific immunotherapy (AIT) is the only allergy treatment that confers long-term symptom amelioration for patients suffering from allergy. The most frequently used allergen application route is subcutaneous injection (SCIT), commonly taken as the gold standard, followed by sublingual (SLIT) or oral (OIT) application of allergen preparations. This is an up-to-date review of the clinical evidence for a novel route of allergen application, i.e., directly into lymph nodes - intralymphatic immunotherapy (ILIT). The major advantages of ILIT over the current AIT approaches are its short duration and the low allergen doses administered. The whole treatment consists of merely 3 ultrasound-guided injections into inguinal lymph nodes 1 month apart. While the number of patients included in randomised controlled trials is still limited, the clinical results for ILIT are encouraging, but more clinical trials are needed, as well as more preclinical work for optimising formulations.
Published online: November 2, 2018
Gesehen am 10.10.2019